Culture of care: the question of animal agency in laboratory animal science - Ameli, Katharina; Krämer, Stephanie (Frontiers in Veterinary Science, 2024)
Background A majority of the current debates in experimental animal science research focus to a large extent on the significance and implementation of the 3Rs principle according to Russell and Burch. In this context, not least due to the EU Directive 2010/63/EU, the concept of a culture of care has become more prevalent. Although animals are essential actors in the field of laboratory science, the discussion around animal agency, as well as the resulting consequences for laboratory animal science, is currently unconsidered. Methods The purpose of this qualitative survey was to identify the perception and understanding of professional workers in laboratory animal science regarding the culture of care in general and aspects of animal agency in particular. Using a non-standardized qualitative survey method (topic-oriented, guideline-based expert interviews), persons involved in animal experimentation in different groups (management, science, regulation, and care) were interviewed. Results Overall, the results of the qualitative survey showed that animal agency plays a subordinate role in the question of a culture of care in animal research. Although not all groups explicitly applied the construct of animal agency or comparable terminology for this, there were links to the theoretical construct. Overall, the interviews showed a recognized network between humans and animals and that animals can interact dialogically in research. This is justified, for example, by the transfer of emotions from carers or scientists to animals. Nevertheless, a differentiated reflection of an animal’s agency remains disregarded. Conclusion The present qualitative survey approached the understanding of a culture of care among experts in the field of animal research. Animal agency does occur in the theoretical reception of the culture of care model. However, it is not conclusively established in everyday practice. Rather, the results lead to the assumption that strategies are being implemented to largely fade out animal agency.